Above- and below-average students think differently: Their scientific argumentation patterns. (December 2019) - Ho, Huei-Ying; Chang, Tzyh-Lee; Lee, Tsu-Nan; Chou, Chin-Cheng; Hsiao, Shih-Hui; Chen, Yu-Hsiang; Lu, Yu-Ling
Highlights: Higher- and lower-achieving students differ in scientific argumentation structures. Higher-achieving students performed better in claim, data, warrant, and backing. Four different clusters of scientific argumentation are indentified. Higher- and lower-achievers show different patterns within the four clusters. Lower-achiever show lower levels of argumentation and need further assistance. Abstract: To understand and help bridge the achievement gap of students especially in terms of scientific argumentation, this paper reports on an analysis of the patterns and differences in the scientific argumentation of 180 grade 4 students (ages 9–10) categorized into 2 levels: above- and below-average. This study developed a way to analyse argumentation skills with its Test of Scientific Argumentation (TSA), which is based on Toulmin's argumentation model. After having students finish tasks under the TSA, the results obtained showed that above-average students performed better in manipulating claim, data, warrant, and backing than below-average students, but all groups had the same performance in rebuttal. Results also revealed that students' learning characteristics could then be divided into four different clusters, from low to high levels of scientific argumentation—randomly intuitive, claim merely, rebuttal reasoning, and near well-structured—with above-average students showing a higher level of argumentation skill. The findings regarding the students' different patterns within the four clusters present implications for curriculum reform, teacher training, and students' differentiated instruction.